Effect of Electrode Distance in Grid Electrode: Numerical Models and In Vitro Tests. (20th March 2018) - Ongaro, Alessia; Campana, Luca Giovanni; De Mattei, Monica; Di Barba, Paolo; Dughiero, Fabrizio; Forzan, Michele; Mognaschi, Maria Evelina; Pellati, Agnese; Rossi, Carlo Riccardo; Bernardello, Clara; Sieni, Elisabetta
Electrochemotherapy is an emerging local treatment for the management of superficial tumors and, among these, also chest wall recurrences from breast cancer. Generally, the treatment of this peculiar type of tumor requires the coverage of large skin areas. In these cases, electrochemotherapy treatment by means of standard small size needle electrodes (an array of 0.73 cm spaced needles, which covers an area of 1.5 cm 2 ) is time-consuming and can allow an inhomogeneous coverage of the target area. We have previously designed grid devices suitable for treating an area ranging from 12 to 200 cm 2 . In this study, we propose different approaches to study advantages and drawbacks of a grid device with needles positioned 2 cm apart. The described approach includes a numerical evaluation to estimate electric field intensity, followed by an experimental quantification of electroporation on a cell culture. The electric field generated in a conductive medium has been studied by means of 3-dimensional numerical models with varying needle pair distance from 1 to 2 cm. In particular, the electric field evaluation shows that the electric field intensity with varying needle distance is comparable in the area in the middle of the 2 electrodes. Differently, near needles, the electric field intensity increases with the increasing electrode distance and supply voltage. The computational results have been correlated with experimental ones obtained in vitro on cell culture. In particular, electroporation effect has been assessed on human breast cancer cell line MCF7, cultured in monolayer. The use of 2-cm distant needles, supplied by 2000 V, produced an electroporation effect in the whole area comprised between the electrodes. Areas of cell culture where reversible and irreversible electroporation occurred were identified under microscope by using fluorescent dyes. The coupling of computation and experimental results could be helpful to evaluate the effect of the needle distance on the electric field intensity in cell cultures in terms of reversible or irreversible electroporation.